Perilaku Perempuan Pemilih dalam Menetapkan Pilihan Pada Pemilu 2009 - T. IRMAYANI (Universitas Sumatera Utara, 2012)
This explaination explain why a voter can emphasize his choice for political party or contestan. For this, of course there are factors that can affect the decision of voter for where is the party who is elected. The focus centre to this explaining is for voter behavior approach to explorate the phenom-ena of women voter behavior and to analyze so able to answer and the factor who influence women for making decision to elect. This study use data that is collection by questionare result and be com-pleted by documentation data. Anda from the researching result show that women voter to make her choice is more be affected by her nearest people (husband, parent, sister, brother) or domestic influ-ence. However, the average of women education is good enough, in gact there is no significant in-fluence to women independentity. If we looking from behavior voter approach, the reason why make a choice to political party or special contestan is becaused by sosiology reason.Keywords: Behavior voter, political participacy, behavior approach.